Pengembangan Potensi Wisata Taman Pujaan Bangsa Margarana Melalui Pelatihan Digital Marketing dan Pelatihan Pemandu Wisata - Ida Bagus Gede Dananjaya; I.G.P. Fajar Pranadi Sudhana; Cokorda Istri Sri Widhari; I Putu Budiarta; Sang Nyoman Bagus Satya Wira (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2024)
The Taman Pujaan Bangsa Margarana National Monument (TPB Margarana) is a memorial monument built to commemorate the Puputan Margarana tragedy. Currently, the number of tourists visiting is still very small, this affects the income obtained is not enough to cover the maintenance and operational costs of TPB Margarana. Digital Marketing Training and Tour Guide Training as an effort to develop the potential of TPB Margarana to increase the number of tourists visiting so that it is expected to have an impact on the sustainability of the TPB Margarana Struggle History Museum. Training and mentoring methods are used in this activity. The training method is designed to convey the important role of digital marketing and tour guide competence to increase the number of visits to TPB Margarana. Digital marketing training and Tour Guide Training were attended by 20 TPB Margarana employees. The output of this activity is in the form of publication of activities through electronic mass media, draft teaching materials and draft community service articles. This activity also provides benefits for TPB Margarana, namely increasing competence in the field of digital marketing and tour guides for TPB Margarana employees and for the Bali State Polytechnic campus as the implementer of activities to share their knowledge with the wider community.